The vital role of arcuate nociceptin/orphanin FQ neurones in mounting an oestradiol‐dependent adaptive response to negative energy balance via inhibition of nearby proopiomelanocortin neurones. (28th October 2022) - Sayers, Sarah; Le, Nikki; Hernandez, Jennifer; Mata‐Pacheco, Veronica; Wagner, Edward J.
Abstract : Abstract: We tested the hypothesis that N/OFQ neurones in the arcuate nucleus (N/OFQ ARC ) inhibit proopiomelanocortin (POMC ARC ) neurones in a diet‐ and hormone‐dependent manner to promote a more extensive rebound hyperphagia upon re‐feeding following an 18 h fast. We utilized intact male or ovariectomized (OVX) female mice subjected to ad libitum ‐feeding or fasting conditions. N/OFQ ARC neurones under negative energy balance conditions displayed heightened sensitivity as evidenced by a decreased rheobase threshold, increased firing frequency, and increased burst duration and frequency compared to ad libitum ‐feeding conditions. Stimulation of N/OFQ ARC neurones more robustly inhibited POMC ARC neurones under fasting conditions compared to ad libitum ‐feeding conditions. N/OFQ ARC inhibition of POMC ARC neurones is hormone dependent as chemostimulation of N/OFQ ARC neurones from fasted males and OVX females produced a sizable outward current in POMC ARC neurones. Oestradiol (E2 ) markedly attenuated the N/OFQ‐induced POMC ARC outward current. Additionally, N/OFQ tonically inhibits POMC ARC neurones to a greater degree under fasting conditions than in ad libitum ‐feeding conditions as evidenced by the abrogation of N/OFQ–nociceptin opioid peptide (NOP) receptor signalling and inhibition of N/OFQ release via chemoinhibition of N/OFQ ARC neurones. Intra‐arcuate nucleus application of N/OFQ further elevated the hyperphagic response and increased meal size during the 6 h re‐feed period, and these effects were mimicked by chemostimulation of N/OFQ ARC neurones in vivo . E2 attenuated the robust N/OFQ‐induced rebound hyperphagia seen in vehicle‐treated OVX females. These data demonstrate that N/OFQ ARC neurones play a vital role in mitigating the impact of negative energy balance by inhibiting the excitability of anorexigenic neural substrates, an effect that is diminished by E2 in females. Key points: Nociceptin/orphanin FQ (N/OFQ) promotes increased energy intake and decreased energy expenditure under conditions of positive energy balance in a sex‐ and hormone‐dependent manner. Here it is shown that under conditions of negative energy balance, i.e. fasting, N/OFQ inhibits anorexigenic proopiomelanocortin (POMC) neurones to a greater degree compared to homeostatic conditions due to fasting‐induced hyperexcitability of N/OFQ neurones. Additionally, N/OFQ promotes a sustained increase in rebound hyperphagia and increase in meal size during the re‐feed period following a fast. These results promote greater understanding of how energy balance influences the anorexigenic circuitry of the hypothalamus, and aid in understanding the neurophysiological pathways implicated in eating disorders promoting cachexia. Abstract : Abstract figure legend Negative energy balance enhances the excitability of orexigenic N/OFQ ARC neurones relative to that seen in sated, ad libitum ‐fed animals. This leads to heightened inhibitory tone onto anorexigenic proopiomelanocortin (POMC) neurones via increased nociceptin opioid peptide (NOP) receptor‐mediated activation of GIRK channels. This in turn leads to an augmented hyperphagic response upon re‐feeding following a prolonged fast that helps to correct the energy balance deficit. The presence of oestradiol (E2 ) in females attenuates the inhibitory actions of N/OFQ.